Space as God’s Presence - Heelan, Patrick A (Journal of Dharma, 1983)
It is not surprising that different individuals, traditions and cultures experience the religious dimension of life in different ways. Since religious experience is a divine communication, the study of religious experience is concerned with channels of communication between God and his peoples; different channels, presumably, serve different cultures and historical communities. I take it that religious experience is an experience of a certain kind—of a religious kind. The phenomenology of this experience, I take to be, that it deals with a sense of loving dependency on some Being other than oneself for life’s ultimate meaning, some Being in whose presence one stands in unqualified awe and with a sense of sin.